Bulk synthesis of linear carbon chains confined inside single‐wall carbon nanotubes by vacuum discharge. (29th November 2018) - Toma, Satoshi; Asaka, Koji; Irita, Masaru; Saito, Yahachi
Abstract : Carbyne, an infinite carbon chain, has attracted much interest and induced significant controversy for many decades. Recently, the presence of linear carbon chains (LCCs), which were confined stably inside double‐wall carbon nanotubes (DWCNTs) and multiwall carbon nanotubes (MWCNTs), has been reported. In this study, we present a novel method to produce LCCs in a film of carbon nanotubes (CNTs). Our transmission electron microscopy and Raman spectroscopy revealed the formation of a bulk amount of LCCs after electric discharge of CNT films, which were used as field emission cathodes. The LCCs were confined inside single‐wall CNTs as well as DWCNTs. Furthermore, two or three LCCs in parallel with each other are encapsulated when the inner diameter of CNT is larger than approximately 1.1 nm.